Performance of newly released pearl millet hybrid MPMH-17 for rain-fed area in Rajasthan - Singh, I.; Kumar, M.; Singh, G.; Kumari, P.; Kumari, S.; Karel, A.; Singh, S. K.; Rohilla, P. P. (Indian Farming, 2019)
Pearl millet hybrid MPMH 17 recently released by Agriculture University, Jodhpur was introduced at 300 farmers’ field in adopted villages (Manai, Binjwadia and Balarwa) of Farmers FIRST Programme (FFP) in 120 ha area during kharif 2017. Pearl millet hybrid MPMH-17 was found superior over the farmers grown varieties and gave seed yield of 20.6 q/ha under rainfed condition which was higher over local by 18.4%. Similarly, straw yield of MPMH 17 was also 20% higher over local. The straw of MPMH-17 remains green till physiological maturity and harvest, therefore the straw appear light green in color compared to local which remains brown to yellow in color. The green color straw has higher preference in market. This hybrid recorded additional net return of ` 6,500/ha over locally grown cultivar. Pearl millet hybrid MPMH-17 was found safe from bird damage at all farmers’ field as it has awns on the ear head and it was also found to be completely disease- and pest-free during the crop pendency.